Multireference state-specific Mukherjee's coupled cluster method with noniterative triexcitations using uncoupled approximation - Bhaskaran-Nair, Kiran; Demel, Ondrej; Smydke, Jan; Pittner, Jirí (The Journal of chemical physics, 2011)
A new version of the multireference Mukherjee's coupled cluster method with perturbative triexcitations has been formulated, which is based on the uncoupled approximation applied to the triples equation. In contrast to the method developed by Evangelista et al. [J. Chem. Phys. 132, 074107 (2010)], the proposed approach does not require to solve the equation for T(3) amplitudes iteratively, yet yields results of essentially the same quality. The method, abbreviated as MR MkCCSD(Tu), has been implemented in the ACES II program package and its assessment has been performed on the BeH(2) model and on the tetramethyleneethane molecule.